The edge-coupler of fiber-to-chip with ultra-low coupling loss based on double-layer silicon waveguides - Ma, Xiaoyue; Hu, Heming; Liu, Shiping; Dong, Runyu; Fang, Qing; Chen, Hua (Frontiers in Physics, 2022)
The edge-coupler of fiber-to-chip with ultra-low coupling loss is demonstrated on SOI platform. The edge-coupler is consisted of the cantilevered SiO2 waveguide, the amorphous silicon(α-Si) nano taper and the crystal silicon(c-Si) nano tapers. The thin α-Si layer is deposited on the c-Si layer to improve the pattern matching with fiber.The optical input signal from the optical fiber is launched into the suspended SiO2 waveguide, then coupled into the α-Si nano taper at the center of the SiO2 waveguide, and finally coupled into the c-Si nano taper.We characterized the cantilevered edge-coupler using cleaved single-mode optical fiber with a mode field diameter of 10.5μm. The measured coupling loss is as low as -1.7dB per facet for TE mode without index matching liquid at 1550nm. The 1dB bandwidth is more than 100 nm with 1dB alignment tolerances of ± 2.0 μm in both horizontal and vertical directions. Besides, potential hybrid optical integration could also be allowed with this results in the future.